2022
DOI: 10.1038/s41598-022-21999-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of γ-irradiation and SBR content in the compatibility of aminated (PVC/LLDPE)/ZnO for improving their AC conductivity and oil removal

Abstract: In some cases, blends containing PVC and LLDPE show low compatibility. Adding styrene-butadiene rubber to the PVC/LLDPE mixtures leads to a noticeable increase in tensile strength and compatibility of the blends. Also, an improvement in tensile strength is observed after incorporating SBR compatibilizer resulting in entirely different gamma irradiation doses. Without a compatibilizer, the mixture exhibits a distributed PVC and LLDPE phase with variable sizes and shapes; even a sizable portion of the domains re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The polymerization process was then carried out utilizing the gamma irradiation approach. The mixed solution was placed into a polyethylene bag and treated with six gamma radiation dosages: (10,20,30,40,50, and 60 kGy). These processes resulted in developing a cross-linked PAAm hydrogel with sodium silicate inside the hydrogel matrix to give (PAAm-Si).…”
Section: Experimental and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerization process was then carried out utilizing the gamma irradiation approach. The mixed solution was placed into a polyethylene bag and treated with six gamma radiation dosages: (10,20,30,40,50, and 60 kGy). These processes resulted in developing a cross-linked PAAm hydrogel with sodium silicate inside the hydrogel matrix to give (PAAm-Si).…”
Section: Experimental and Materialsmentioning
confidence: 99%
“…These absorbers do have certain drawbacks, though. For instance, inorganic sorbents displayed some intrinsic limits due to their high density and low oil sorption capabilities. , The bulk of naturally occurring organic sorbents had a low hydrophobicity, or capacity to repel water, which led to high water uptake. Development of novel sorbents with advantages in sorption capacity, selectivity, density, recyclability, hydrophobicity, lipophilia, and environmental friendliness was therefore necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of LLDPE nanocomposites for oil removal is an active area of research 7 . Also, (LLDPE) coated polyvinyl alcohol (PVA) nanofibrous membrane to make it superhydrophobic and Superoleophilic 8 .…”
Section: Introductionmentioning
confidence: 99%
“…(3) the addition of low molecular weight additives interacting with both blend components. Sharshir et al [5] reported PVC and HPPE blends compatibilization by gamma irradiation in the dose of 0, 10 and 20 kGy. They showed remarkable improvement in mechanical properties after the gamma irradiation process.…”
Section: Introductionmentioning
confidence: 99%